2018
DOI: 10.5731/pdajpst.2017.008342
|View full text |Cite
|
Sign up to set email alerts
|

Usability of the Ranibizumab 0.5 mg Prefilled Syringe: Human Factors Studies to Evaluate Critical Task Completion by Healthcare Professionals

Abstract: Both the simulated-use and actual-use usability studies yielded consistent data, showing that healthcare professionals are able to use the ranibizumab PFS by successfully performing all critical tasks involved in preparing and delivering an intravitreal injection. The simulated-use usability testing was sufficiently realistic and representative of real-world use, and was appropriate and preferred over actual-use usability testing for proper evaluation of the product user interface. Ranibizumab is approved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Notably, tip cap inspection was not considered an Essential or Safety Critical Task in formative or summative testing of the ranibizumab PFS (26). Most of the remaining use errors were related to lack of frequent experience with PFS devices for IVI, transference behaviors from existing products, or incorrect technique around the IVI procedure itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, tip cap inspection was not considered an Essential or Safety Critical Task in formative or summative testing of the ranibizumab PFS (26). Most of the remaining use errors were related to lack of frequent experience with PFS devices for IVI, transference behaviors from existing products, or incorrect technique around the IVI procedure itself.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these complications have been associated with medication preparation (8)(9)(10)(11)(12), and particular concern has been raised regarding introduction of silicone oil (SO) droplets into the eye from silicone-lubricated syringes used during the procedure (13-25), especially when conventional hypodermic syringes are used. These issues have spurred the development of delivery devices intentionally designed for IVI, such as the recently approved ranibizumab prefilled syringe (PFS) (26). Use of PFSs to deliver IVIs offers the potential to reduce injection time, lower the risk of contamination, endophthalmitis, intraocular air bubbles, and SO droplets, and increase dosing accuracy (8,(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using the PFS, the physician simply removes the syringe cap, attaches the injection needle, and adjusts the dose prior to administration. Retina specialists and ophthalmic medical personnel have successfully performed both simulated-use and actual-use usability studies (with the PFS) with reported ease and without any critical errors 14. Reduction in these steps in the administration of intravitreal injections comes with some advantages which are detailed in the following sections.…”
Section: Ranibizumab Pfs Injection Technique and Ease Of Administrationmentioning
confidence: 99%